A MRI study of the lesser trochanteric version and its relationship to proximal femoral osseous anatomy - Schröder, Ricardo Gonçalves (J Hip Preserv Surg, 2015)
The purpose of this study is to quantify the lesser trochanteric version and determine the angle and the relationship between lesser trochanter and femoral neck version. Investigate the influence of the lesser trochanter version in the width of ischiofemoral space. Two hundred and fifty asymptomatic hips were evaluated with axial magnetic resonance image. The lesser trochanter version was calculated. The difference between the femoral neck version and the lesser trochanter version formed the angle between each structure. The width of ischiofemoral space was measured and its relationship with the lesser trochanter version was determined. The mean lesser trochanter version was −24° ± 11.5° (range, − 54° to + 17°) with a coefficient variation of 47.45%. The mean femoral neck version measured 14.0° ± 10.8° (range, −16° to 50°), with a coefficient variation of 81.32%. The lesser trochanter/femora neck angle was 38.4° ± 9.6° (range, 8° to 67°), coefficient variation of 30%, with a moderate correlation between the structures (r = 0.63, P < 0.01). The mean ischiofemoral space was 22.9.0 ± 7.0 mm (range, 10.3 to 55 mm), and a weak correlation was found between ischiofemoral space and lesser trochanteric version (r = −0.16, P < 0.05). The lesser trochanteric version showed a high variation with a moderate relationship with the femoral neck version. The lesser trochanteric version does not influence the width of the ischiofemoral space.